Disentangling the Stern/Nordhaus controversy: Beyond the discounting clash - Etienne Espagne; Baptiste Perrissin Fabert; Antonin Pottier; Franck Nadaud; Patrice Dumas (Fondazione Eni Enrico Mattei (FEEM), 2012)
The Stern/Nordhaus controversy has polarized the widely disparate beliefs about what to do in order to tackle the climate challenge. To explain differences in results and policy recommendations, comments following the publication of the Stern Review have mainly focused on the role played by the discount rate. A closer look at the actual drivers of the controversy reveals however that Stern and Nordhaus also disagree on two other parameters: technical progress on abatement costs and the climate sensitivity. This paper aims at appraising the relative impacts of such key drivers of the controversy on the social cost of carbon and climate policy recommendations. To this end, we use the flexible integrated assessment model RESPONSE which allows us to compare very diverse worldviews, including Stern and Nordhaus' ones within the same modelling framework and map the relative impacts of beliefs on the three key drivers of the controversy. Furthermore we appraise quantitatively, by means of a linear statistical model, the impacts on results of an extended set of core parameters of RESPONSE. We show that beliefs on long term economic growth, technical progress, the form of the climate damage function and the climate sensitivity have an impact as important as beliefs on pure time preference. Hence, we can qualify the role played by the discount rate in the Stern/Nordhaus controversy and more broadly in the definition of climate policies.
Keywords: Q54; Q58; C61; 330; Integrated Assessment Model; Discount Rate; Social Cost of Carbon; Abatement Policy; Worldview